1997
DOI: 10.1007/bf03030455
|View full text |Cite
|
Sign up to set email alerts
|

Development of cambium and length of vessel elements and fibers in dwarfAlnus hirsuta (Spach) rupr

Abstract: In a comparison of cambial cells and their derivatives between naturally occurring dwarf and normal trees, vessel elements and fibers in the annual rings of dwarf trees were found to be shorter, narrower and fewer than those of normal trees. The frequency of anticlinal divisions and loss of cambial initials were low during the differentiation of xylem cells from cambial initials in dwarf trees. The length and intrusive growth of fusiform initials were slightly less than those of normal trees. Thus, it was conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The increased vessel proportion in the wood, despite a reduction in dimensions of vessel elements as recorded in this study ( Table 5), indicates that vessels differentiated in larger numbers in the polluted atmosphere, possibly as part of an adaptive strategy. Since the size of fusiform cambial initials changes under the influence of environmental conditions (Iqbal and Ghouse 1990), the shortening of vessel elements and xylem fibers under pollution stress could be due to either a reduced length of their precursor fusiform initials, or a reduced capacity of differentiating wood elements to elongate under stressful conditions (Lim and Soh 1997). Studies on mango trees growing under coal-smoke pollution have suggested that the length of vessel elements could be more sensitive to pollutants than their width, or that the morphogenetic factors controlling the vessel-element length were the first to be impaired by the pollutants (Gupta and Iqbal 2005).…”
Section: Cambial Growth and Wood Productionmentioning
confidence: 99%
“…The increased vessel proportion in the wood, despite a reduction in dimensions of vessel elements as recorded in this study ( Table 5), indicates that vessels differentiated in larger numbers in the polluted atmosphere, possibly as part of an adaptive strategy. Since the size of fusiform cambial initials changes under the influence of environmental conditions (Iqbal and Ghouse 1990), the shortening of vessel elements and xylem fibers under pollution stress could be due to either a reduced length of their precursor fusiform initials, or a reduced capacity of differentiating wood elements to elongate under stressful conditions (Lim and Soh 1997). Studies on mango trees growing under coal-smoke pollution have suggested that the length of vessel elements could be more sensitive to pollutants than their width, or that the morphogenetic factors controlling the vessel-element length were the first to be impaired by the pollutants (Gupta and Iqbal 2005).…”
Section: Cambial Growth and Wood Productionmentioning
confidence: 99%